Parents' challenges against the intention of the implementation of the 12-year compulsory education policy in Malaysia - Juliana Mohd Janjang,; Mohamed Yusoff Mohd Nor,; Aida Hanim A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Compulsory education policies supported by the law have been implemented throughout the world for centuries, including in Malaysia. However, the implementation of the law is only limited to 6 years of compulsory education at the primary level as opposed to at the international level, which reaches a period of 8 to 12 years of compulsory schooling. Therefore, this study was conducted to explore the challenges faced by parents if Malaysia intends to implement compulsory education in Malaysia within a period of 12 years, starting from one year in preschool until the end of schooling at the secondary level. This study was conducted using a qualitative approach involving several participants selected through purposive sampling. The exploration results through open-ended questions, focus group discussions, and researcher notes were analysed using a thematic analysis, which then received expert consensus at an excellent level with a Cohen Kappa index value exceeding 0.81. The study discovered four themes of challenges faced by parents in implementing the 12-year compulsory education policy in Malaysia, namely parents' financial issues, school-related issues that are a challenge for parents, parents' difficulty in managing their children, and issues faced by children, all of which have resulted in challenges to parents. In this vein, these challenges should be emphasized because parents are the main implementers of the compulsory education policy, which also determines the success of the intended 12-year compulsory education policy.